The anisotropy of oxygen vacancy migration in SrTiO3. (13th May 2016) - Hanzig, Juliane; Zschornak, Matthias; Mehner, Erik; Hanzig, Florian; Münchgesang, Wolfram; Leisegang, Tilmann; Stöcker, Hartmut; Meyer, Dirk C
Abstract: Oxygen migration in perovskites is well known to occur via vacancies along the TiO6 octahedron edges. Ionic conduction depends further on the orientation of the crystal in the electric field. To study the anisotropy in cubic SrTiO3 single crystals, temperature-dependent electroformation measurements ranging from 11 °C to 50 °C have been conducted for representative crystallographic directions within the crystal system. Electroformation of pure SrTiO3 follows an Arrhenius behavior, implying an ionic migration process of intrinsic oxygen defects. Activation energies E A for oxygen vacancy migration have been determined to 0.70 eV for 〈 0 0 1 〉 and 〈 1 1 0 〉 directions in contrast to 0.77 eV for 〈 1 1 1 〉 . Mobility of oxygen vacancies is enhanced in 〈 0 0 1 〉 compared to 〈 1 1 0 〉 and 〈 1 1 1 〉 by up to half an order of magnitude. A migration model based on atomistic migration paths and their multiplicities accounts for these experimental variations in mobility.